Underestimated Passive Volcanic Sulfur Degassing Implies Overestimated Anthropogenic Aerosol Forcing - Jongebloed, U. A.; Schauer, A. J.; Cole-Dai, J.; Larrick, C. G.; Wood, R.; Fischer, T. P.; Carn, S. A.; Salimi, S.; Edouard, S. R.; Zhai, S.; Geng, L.; Alexander, B. (Digital Commons @ Michigan Tech, 2023)
The Arctic is warming at almost four times the global rate. An estimated sixty percent of greenhouse-gas-induced Arctic warming has been offset by anthropogenic aerosols, but the contribution of aerosols to radiative forcing (RF) represents the largest uncertainty in estimating total RF, largely due to unknown preindustrial aerosol abundance. Here, sulfur isotope measurements in a Greenland ice core show that passive volcanic degassing contributes up to 66 ± 10% of preindustrial ice core sulfate in years without major eruptions. A state-of-the-art model indicates passive volcanic sulfur emissions influencing the Arctic are underestimated by up to a factor of three, possibly because many volcanic inventories do not include hydrogen sulfide emissions. Higher preindustrial volcanic sulfur emissions reduce modeled anthropogenic Arctic aerosol cooling by up to a factor of two (+0.11 to +0.29 W m−2), suggesting that underestimating passive volcanic sulfur emissions has significant implications for anthropogenic-induced Arctic climate change.